P'yem vodu rodnogo dnepra, budem pit' iz Pruta, Nemana i Buta! - Ivanov, Viktor Semonovich (Изобразительное искусство, 1943)
Red Army soldier drinking water from helmet Original title: Пьем воду родного днепра, будем пить из Прута, Немана и Бута!. Suggested translation: We drink waters of our Dnieper, we will drink from Prut, Niemen and Bug too! PO-0059